Population structures of Leishmania infantum and Leishmania tropica the causative agents of kala-azar in Southwest Iran - Ghatee, M; Mirhendi, H; Karamian, M; Taylor, W; Sharifi, I; Hosseinzadeh, M; Kanannejad, Z (Springer, 2018)
Visceral leishmaniasis (VL) is endemic in Iran and is caused predominantly by Leishmania infantum, but L. tropica is emerging as an important cause. We studied the intra-species population structure of Leishmania spp. causing VL in southwest Iran by sequence analysis of the internal transcribed spacer (ITS) 1 of DNA samples from 29 bone marrow aspiration smears. L. infantum (n = 25) and L. tropica (n = 4) were identified, consisting of 10 and three ITS1 sequence types (STs), respectively. Compared to GenBank ITS1 STs, our L. infantum parasites displayed high heterogeneity but less heterogeneity compared than northwest Iranian isolates. VL affects mostly nomadic populations in southwest Iran, and their mobility may explain partly the L. infantum heterogeneity. The VL causing L. tropica was also genetically heterogeneous but genetically indistinguishable from L. tropica strains causing anthroponotic cutaneous leishmaniasis from southwest Iran.